2006
DOI: 10.1038/ng1877
|View full text |Cite
|
Sign up to set email alerts
|

Wnk4 controls blood pressure and potassium homeostasis via regulation of mass and activity of the distal convoluted tubule

Abstract: The mechanisms that govern homeostasis of complex systems have been elusive but can be illuminated by mutations that disrupt system behavior. Mutations in the gene encoding the kinase WNK4 cause pseudohypoaldosteronism type II (PHAII), a syndrome featuring hypertension and hyperkalemia. We show that physiology in mice transgenic for genomic segments harboring wild-type (TgWnk4(WT)) or PHAII mutant (TgWnk4(PHAII)) Wnk4 is changed in opposite directions: TgWnk4(PHAII) mice have higher blood pressure, hyperkalemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
343
4
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(379 citation statements)
references
References 30 publications
27
343
4
1
Order By: Relevance
“…Available hypotheses view WNK4 (and the isoforms of WNK1) as partners of a multiprotein complex that involves the homo-and heteromultimers of WNKs that exert scaffolding and kinase functions on downstream target proteins. Mice bearing a transgene with the human PHA2-mutant WNK4 develop hypertension, hyperkalemia and hypercalciuria, with dramatic structural changes of the distal convoluted tubule, including hyperplasia and massive expression of NCC (Lalioti et al 2006). This group suggested that PHA2B-causing mutations in negatively charged domains of WNK4 affect the ability to sense intracellular Ca 2+ levels, e.g.…”
Section: Gordon's Syndrome (Pseudohypoaldosteronism Type Ii)mentioning
confidence: 99%
See 1 more Smart Citation
“…Available hypotheses view WNK4 (and the isoforms of WNK1) as partners of a multiprotein complex that involves the homo-and heteromultimers of WNKs that exert scaffolding and kinase functions on downstream target proteins. Mice bearing a transgene with the human PHA2-mutant WNK4 develop hypertension, hyperkalemia and hypercalciuria, with dramatic structural changes of the distal convoluted tubule, including hyperplasia and massive expression of NCC (Lalioti et al 2006). This group suggested that PHA2B-causing mutations in negatively charged domains of WNK4 affect the ability to sense intracellular Ca 2+ levels, e.g.…”
Section: Gordon's Syndrome (Pseudohypoaldosteronism Type Ii)mentioning
confidence: 99%
“…Adrenal aldosterone release is stimulated either by volume contraction or hyperkalemia, situations which require different adaptations (sodium and water uptake vs sodium uptake coupled to potassium excretion) of the kidneys despite an identical signal. WNK4 activity could be the switch for this adaptation (Lalioti et al 2006).…”
Section: Gordon's Syndrome (Pseudohypoaldosteronism Type Ii)mentioning
confidence: 99%
“…Deletion of the Na + Cl − cotransporter (NCC) reversed most of the phenotypes seen in the transgenic mice harboring the PHAII-causing WNK4 mutants (5), which indicated that aberrant regulation of NCC by the mutant WNK4 is critically involved in the pathogenesis of PHAII. This finding led to the suggestion that increased Na + in systemic fluids by the altered NCC activity is associated with elevated blood pressure (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…To date, a direct link between a particular gene impinging histone modifications to BP has not been clearly established. Second, numerous mouse models lacking ENaC and their direct or indirect regulators such as AS, 13 angiotensinogen (Agt), 14 angiotensin-converting enzyme (ACE), 15 MR, 16 Sgk1, 17 WNK1, 18 WNK4, 19 and Period 20 have been reported. However, the role of these models in showing the epigenetic control of BP is still unclear.…”
mentioning
confidence: 99%